The clinical efficacy of scalp acupuncture for tinnitus: A systematic review and meta-analysis - Jiadi Chen; Ruizhi Jing (Complementary Therapies in Medicine)
Background: No single treatment is considered to be universally effective for tinnitus. Scalp acupuncture has been explored as a potential treatment. Objective: This systematic review and meta-analysis aim to evaluate the clinical efficacy of scalp acupuncture in treating tinnitus. Methods: A comprehensive search of relevant databases was conducted to identify randomized controlled trials comparing scalp acupuncture with a control treatment for tinnitus.The clinical efficacy rate and reduction in tinnitus severity were assessed using relative risk (RR) and standardized mean difference (SMD), respectively. Sensitivity analyses was performed to investigate sources of heterogeneity. Results: A total of 20 research studies,with 1430 participants,were included.The systematic review and meta-analysis revealed that the scalp acupuncture groups had a significantly higher clinical effective rate compared to the control groups (RR=1.25, 95 % CI 1.16–1.35, p < 0.00001),with low heterogeneity(p = 0.27,I2=20 %).The scalp acupuncture groups and scalp acupuncture plus auxiliary acupoints groups had greater reduction in tinnitus severity compared to the control groups(SMD=-0.76,95 %CI:-1.02,-0.51,p < 0.00001;SMD:-0.93,95 %CI:-1.52,-0.33,p = 0.002, respectively),with a moderate heterogeneity(p = 0.005,I2=62 %) and a significant heterogeneity (p < 0.00001,I2=86 %) observed due to differences in study design, sample characteristics, and intervention protocols.Sensitivity analysis confirmed the stability of the results.The summary table generated through GRADEpro indicated that the certainty of evidence ranged from moderate to low. Conclusions: Scalp acupuncture has demonstrated promising efficacy in the treatment of tinnitus compared to traditional acupuncture or pharmacotherapy. However, the current evidence is limited due to potential biases and heterogeneity across studies.Future studies should standardize protocols, ensure higher methodological rigor, and explore long-term effects to validate the findings further.The review was registered with PROSPERO (CRD42024537806):Jiadi Chen, Ruizhi Jing.Analysis of clinical effect of scalp acupuncture on tinnitus. Availablefrom: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024537806.